Young People and the Management of Chronic Illness by Primary Care Pharmacists: A Systematic Review - Mohammed Almunef; Julie Mason; Chris Curtis; Zahraa Jalal (MDPI AG, 2019)
Recent evidence has shown that the incidence of long-term illnesses in young people aged 10−24 years is increasing. It is essential to highlight the importance of long-term health conditions in this age group and understand young people’s health needs to be able to improve current support for young people. Pharmacists, as medicine experts, are in a unique position to promote young people’s health. The role of primary care pharmacists in the management of chronic illnesses in young people has not been widely researched. The aim of this review was to explore the current role of primary care pharmacists in the management of chronic illnesses in young people aged 10−24 years. A systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement using Medical Subject Headings (MeSH) and Embase subject headings (Emtree) terms, covering three main themes: Pharmacists, young people and chronic illnesses. Articles were critically appraised using Critical Appraisal Skills Programme (CASP) tools. Eight articles were included in this review. Seven articles included original research studies (one observational study, two surveys, two qualitative interview studies and two interventions). The remaining article was a literature review. All of the articles made reference to community pharmacists, while there was no information about GP pharmacists. Roles that community pharmacists identified as high-priority in their practice when dealing with young people included supporting young people to develop generic healthcare skills, counselling and building trusted relationships directly with young people, helping young people to find credible health information and the provision of specialist services. Community pharmacists feel that they have a role to play in supporting young people with chronic illness and have identified many areas where they can provide services and support.